Breakpoint characterization of large deletions in EXT1 or EXT2 in 10 Multiple Osteochondromas families - Szuhai Karoly; Hogendoorn Pancras CW; Mees Kirsten; de Jong Danielle; Jennes Ivy; Wuyts Wim (BMC, 2011)
Abstract Background Osteochondromas (cartilage-capped bone tumors) are by far the most commonly treated of all primary benign bone tumors (50%). In 15% of cases, these tumors occur in the context of a hereditary syndrome called multiple osteochondromas (MO), an autosomal dominant skeletal disorder characterized by the formation of multiple cartilage-capped bone tumors at children's metaphyses. MO is caused by various mutations in EXT1 or EXT2, whereby large genomic deletions (single-or multi-exonic) are responsible for up to 8% of MO-cases. Methods Here we report on the first molecular characterization of ten large EXT1- and EXT2-deletions in MO-patients. Deletions were initially indentified using MLPA or FISH analysis and were subsequently characterized using an MO-specific tiling path array, allele-specific PCR-amplification and sequencing analysis. Results Within the set of ten large deletions, the deleted regions ranged from 2.7 to 260 kb. One EXT2 exon 8 deletion was found to be recurrent. All breakpoints were located outside the coding exons of EXT1 and EXT2. Non-allelic homologous recombination (NAHR) mediated by Alu-sequences, microhomology mediated replication dependent recombination (MMRDR) and non-homologous end-joining (NHEJ) were hypothesized as the causal mechanisms in different deletions. Conclusions Molecular characterization of EXT1- and EXT2-deletion breakpoints in MO-patients indicates that NAHR between Alu-sequences as well as NHEJ are causal and that the majority of these deletions are nonrecurring. These observations emphasize once more the huge genetic variability which is characteristic for MO. To our knowledge, this is the first study characterizing large genomic deletions in EXT1 and EXT2.